Analisis Pengungkapan Standar Akuntansi Syariah Aaoifi Pada Bank Syariah Di Indonesia Dan Malaysia Periode Tahun 2017-2018 - Fajar Yufrikal Azlan1; Vanica Serly (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to examine the compliance of AAOIFI sharia accounting standards disclosures in Islamic Banks in Indonesia and Malaysia in 2017 and 2018. This study measures compliance by looking at three Islamic banks' products in Islamic, mudaraba, and musharaka. Data was collected from the annual report of 12 Islamic commercial banks in Indonesia and 15 Islamic commercial banks in Malaysia for 2017 and 2018. The data collection method in this study is the documentation study. Analysis of the data used is descriptive statistics. This study found that the disclosure of Islamic banks related to murabahah, mudharabah and musyarakah is still relatively low. There was no difference in compliance levels between the two countries during the periods of 2107 and 2018. Among the three Islamic bank products, murabaha has the highest mean. In addition, Islamic banks in Indonesia as a whole have a higher level of disclosure than Islamic banks in Malaysia.